2019
DOI: 10.1002/smll.201903643
|View full text |Cite
|
Sign up to set email alerts
|

Protonation‐Assisted Exfoliation of N‐Containing 2D Conjugated Polymers

Abstract: natural incorporation into the conjugated polymer frameworks mainly comprised of carbon atoms. [8][9][10][11] Consequently, the optoelectronic properties can be conveniently tailored in N-containing 2D conjugated polymers through different synthetic routes using different organic building blocks.On the other hand, compared to bulk 2D polymers, ultrathin nanosheets (<10 nm in thickness) are highly favorable for photocatalytic applications as the ultrathin feature offers several unique advantages in photocatalys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 55 publications
2
22
0
Order By: Relevance
“…The unique advantages of 2D NPMB nanosheet catalysts are concluded as follows: 1) the ultrathin 2D nanosheet structure with atomic thickness and large specific surface has the maximum possible numbers of exposed active sites; meanwhile, the exposed numbers of active sites is comparable to that of the whole atoms of monolayer [ 3,53,77 ] ; 2) the ultrathin 2D nanosheet structure, with numerous defects and unsaturated metal sites that arise from the delamination process, can facilitate the adsorption and desorption of reaction intermediates of water splitting; [ 48,78–80 ] 3) the ultrathin 2D nanosheet structure, with unique electronic structures of atom level, shortens the electron‐transfer path and reduces the free energy of elemental steps in HER and OER processes; [ 15,55,81,82 ] 4) the ultrathin 2D nanosheet structure, with marvelous accessible surface area, can serve them as the ideal platforms to combine other catalytic materials, to further adjust the states of electronic structures, so as to boost electrochemical behavior, i.e., heterostructure built with different unilamellar catalysts that own the diverse intrinsic advantages. [ 55,83–85 ] Besides, the ultrathin 2D nanosheet structure with atomic thickness is also an effective model for studying the real active species of NPMB nanosheet catalysts during the electrocatalytic reaction process, especially for the OER process in alkaline media. As can be seen from recent related examples, [ 86–92 ] the dynamics of electrocatalytic process of catalysts strongly depend on the external structure (morphology, crystallization, etc.)…”
Section: Advantages Of 2d Npmb Nanosheet Electrocatalysts For Water Splittingmentioning
confidence: 99%
“…The unique advantages of 2D NPMB nanosheet catalysts are concluded as follows: 1) the ultrathin 2D nanosheet structure with atomic thickness and large specific surface has the maximum possible numbers of exposed active sites; meanwhile, the exposed numbers of active sites is comparable to that of the whole atoms of monolayer [ 3,53,77 ] ; 2) the ultrathin 2D nanosheet structure, with numerous defects and unsaturated metal sites that arise from the delamination process, can facilitate the adsorption and desorption of reaction intermediates of water splitting; [ 48,78–80 ] 3) the ultrathin 2D nanosheet structure, with unique electronic structures of atom level, shortens the electron‐transfer path and reduces the free energy of elemental steps in HER and OER processes; [ 15,55,81,82 ] 4) the ultrathin 2D nanosheet structure, with marvelous accessible surface area, can serve them as the ideal platforms to combine other catalytic materials, to further adjust the states of electronic structures, so as to boost electrochemical behavior, i.e., heterostructure built with different unilamellar catalysts that own the diverse intrinsic advantages. [ 55,83–85 ] Besides, the ultrathin 2D nanosheet structure with atomic thickness is also an effective model for studying the real active species of NPMB nanosheet catalysts during the electrocatalytic reaction process, especially for the OER process in alkaline media. As can be seen from recent related examples, [ 86–92 ] the dynamics of electrocatalytic process of catalysts strongly depend on the external structure (morphology, crystallization, etc.)…”
Section: Advantages Of 2d Npmb Nanosheet Electrocatalysts For Water Splittingmentioning
confidence: 99%
“…In order to address this issue, Zhang's group developed a protonation‐assisted LPE method to improve the exfoliation yield of various N‐containing 2D polymer nanosheets from only 2–15% in pure water to 41–56% in 12 m HCl. [ 29 ] The achieved ultrathin nanosheets had an average thickness of less than 5 nm, showing good dispersion in aqueous solutions. The high yield could be attributed to the fact that the presence of concentrated HCl would lead to the protonation of the N‐containing sites within the frameworks, which can produce strong electrostatic repulsion effect between adjacent layers and form hydrogen bonds with water molecules so that the neighboring layers within the bulk polymer could be easily exfoliated into ultrathin nanosheets.…”
Section: Preparation Of 2d Polymer Nanosheetsmentioning
confidence: 99%
“…In 2019, X. Zhang et al reported 41%-56% exfoliation yields for C 3 N 4 , C 2 N, and aza-CMP in acid media (Zhang et al, 2019). In their work, C 2 N was also synthesized using HAB and HKH in NMP.…”
Section: Nmentioning
confidence: 99%